2014
DOI: 10.1074/jbc.m114.609800
|View full text |Cite
|
Sign up to set email alerts
|

Co- and Post-translocation Roles for HSP90 in Cholera Intoxication

Abstract: Background:The unfolded A1 subunit of cholera toxin (CT) enters the host cytosol by passing through a pore in the endoplasmic reticulum (ER) membrane. Results: ATP-dependent refolding of CTA1 by Hsp90 is sufficient for toxin export to the cytosol. Conclusion: Hsp90 couples CTA1 refolding with CTA1 extraction from the ER. Significance: This work provides a molecular basis for toxin translocation into the host cytosol.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(65 citation statements)
references
References 67 publications
1
61
0
3
Order By: Relevance
“…Although initial reports suggested that CTA1 requires Derlin-1 for retrotranslocation from the ER into the cytosol based on the DN Derlin-1 construct used here, this conclusion is being reconsidered (53, 55). Conformational changes in CTA1 may directly lead to its recognition by the E3 ligase Hrd1 and associated Sel1L protein to mediate retrotranslocation (70), perhaps using Hsp90 and its ATPase activity to promote ER membrane extraction and rapid folding at the cytosolic face of the ER membrane (71, 72). Rapid refolding has been proposed to prevent recognition of CTA1 by the proteasome (73).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although initial reports suggested that CTA1 requires Derlin-1 for retrotranslocation from the ER into the cytosol based on the DN Derlin-1 construct used here, this conclusion is being reconsidered (53, 55). Conformational changes in CTA1 may directly lead to its recognition by the E3 ligase Hrd1 and associated Sel1L protein to mediate retrotranslocation (70), perhaps using Hsp90 and its ATPase activity to promote ER membrane extraction and rapid folding at the cytosolic face of the ER membrane (71, 72). Rapid refolding has been proposed to prevent recognition of CTA1 by the proteasome (73).…”
Section: Discussionmentioning
confidence: 99%
“…Further, the cytosolic p97 ATPase has been reported to provide the energy for membrane extraction of many ERAD substrates (2, 13), and yet this enzyme is dispensable for CTA1 dislocation to the cytosol (64, 65, 67). More recently, the chaperone Hsp90 has been shown to bind to CTA1 to facilitate its extraction from the ER membrane as well as rapid folding in the cytosol, at least in cell-free systems (71), but others dispute this claim (74). Membrane extraction of most ERAD substrates by the AAA ATPase p97 is followed by E3 ligase-mediated polyubiquitylation (5).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, Hsp90 has been suggested to provide the ratchet mechanism for the A1 fragment by coupling the dislocation process with chaperone-assisted refolding of the polypeptide [146]. Recent data provide experimental support for this mechanism and further suggest that HSP90 remains bound to A1, even after refolding [147]. In addition, HSP90 may prevent ubiquitination of the toxins [143,146].…”
Section: Translocation Across the Er Membranementioning
confidence: 99%
“…Although it has been claimed that Hsp90 is a candidate for the extraction reaction (Taylor et al, 2010, Burress et al, 2014), an unbiased fractionation approach suggested that Hsp90 does not mediate this step (Moore et al, 2013). Instead, a GTP-dependent activity might provide the energy to dislocate the toxin from the ER membrane (Moore et al, 2013).…”
Section: Bacterial Toxinmentioning
confidence: 99%